2006
DOI: 10.1159/000095441
|View full text |Cite
|
Sign up to set email alerts
|

Depression Vulnerabilities in Patients with Different Levels of Depressive Symptoms after Acute Coronary Syndromes

Abstract: Background: Cognitive, behavioral, and interpersonal vulnerabilities have been studied in patients fulfilling diagnostic criteria for major depression and dysthymia. The extent to which these vulnerabilities are present in cardiac patients with mild to moderate depressive symptoms – a risk factor for mortality – is unknown. Moreover, few studies have examined interrelations among depression vulnerabilities. Methods: A consecutive cohort of 314 patients with acute coronary syndrome completed the Beck Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 66 publications
5
39
0
Order By: Relevance
“…Furthermore, aetiological studies have established an association between depressive symptoms and incident CHD in initially healthy individuals, as demonstrated in systematic reviews (Rugulies, 2002;Wulsin & Singal, 2003). The findings of Rieckmann et al (2006) outlined above, which show that depressed ACS patients exhibit the theoretical vulnerabilities to depression, also indicate that depression is present prior to the cardiac event in a substantial number of patients. As these vulnerabilities would have been present prior to the ACS event, and they are theoretically unrelated to CHD, one could therefore argue that these patients are depressed independently of CHD severity.…”
Section: Future Directionsmentioning
confidence: 87%
See 4 more Smart Citations
“…Furthermore, aetiological studies have established an association between depressive symptoms and incident CHD in initially healthy individuals, as demonstrated in systematic reviews (Rugulies, 2002;Wulsin & Singal, 2003). The findings of Rieckmann et al (2006) outlined above, which show that depressed ACS patients exhibit the theoretical vulnerabilities to depression, also indicate that depression is present prior to the cardiac event in a substantial number of patients. As these vulnerabilities would have been present prior to the ACS event, and they are theoretically unrelated to CHD, one could therefore argue that these patients are depressed independently of CHD severity.…”
Section: Future Directionsmentioning
confidence: 87%
“…Cognitive models of depression have been investigated in cardiac patients (Berkman et al, 2003;Carney et al, 2004;de Jonge, Ormel, et al, 2006;Dijkstra et al, 2002;Rieckmann et al, 2006;Roberts, 1989;Shnek, Irvine, Stewart, & Abbey, 2001). Rieckmann et al (2006) demonstrated that mildly to moderately/severely depressed patients with ACS had significantly higher levels of dysfunctional attitudes compared to non-depressed ACS patients.…”
Section: Associations With Depression and Chdmentioning
confidence: 99%
See 3 more Smart Citations